ROLE OF TOLL-LIKE RECEPTORS AND THEIR ENDOGENOUS LIGANDS IN THE PATHOGENESIS OF RHEUMATOID ARTHRITIS: A REVIEW OF LITERATURE - M. Yu. Volkov (Научно-практическая ревматология, 2016)
Despite great advances in the study of the pathogenesis of rheumatoid arthritis (RA), which could design a radically new class of fundamentally sound therapeutic agents, many immunological aspects remain fully unstudied. The role of innate immunity mechanisms in the development of autoimmune inflammation is one of the important issues in the pathogenesis of not only RA, but also all rheumatic diseases. The discovery of pattern recognition receptors (PRRs) has allowed fundamental immunology to make a great stride toward understanding how these mechanisms are implemented. The study of membranous and endosomal Toll-like receptors (TLRs), the most extensive and well-studied group of PRRs, is a promising area of modern rheumatology. It is significant to note that some molecular agents, the presence of which in tissue is associated with its damage, are able to stimulate TLRs. They have received the name damage-associated molecular patterns (DAMPs). The paper provides a review of the literature on the mechanisms of TLR-mediated signaling pathways, on different aspects of a role of individual TLRs and DAMPs in the induction and maintenance of autoimmune inflammation in RA, and on prospects for targeted therapy aimed at inhibiting some TLRs and DAMPs.